Analisis dan Peningkatan Keamanan Cyber: Studi Kasus Ancaman dan Solusi dalam Lingkungan Digital Untuk Mengamankan Objek Vital dan File - Edy Soesanto; Achmad Romadhon; Bima Dwi Mardika; Moch Fahmi Setiawan (Institut Nalanda, 2023)
The threat to vital objects and file security is rapidly evolving. Cybercriminals are becoming more cunning and skilled at exploiting security vulnerabilities in digital systems. In order to enhance cybersecurity, a thorough analysis of the threats faced in the digital environment and the applicable solutions is necessary. The objectives of this research are to analyze vital objects, identify key challenges in protecting them from cyber attacks, evaluate and propose measures and strategies to improve file security, and examine case studies related to threats and solutions in the digital environment.This research adopts a qualitative approach using interview and observation techniques. Potential cybercrime threats in Indonesia include hacking, cracking, cyber sabotage, and spyware. The risk management process involves identifying, assessing, treating, and controlling risks. To anticipate these threats, it is essential to have technology experts who support the development of advanced national defense systems and establish a cybersecurity command center.